Plan de marketing comunicacional para fomento del turismo en el cantón Quevedo, periodo 2015-2019 - Miño Llaguno, Jocasta Paola (2015)
The thesis project developed, was aimed to: Develop a Marketing Plan for the Promotion of Communicative Canton Tourism Quevedo, so the effect was formulated and applied goals that allowed the generation prior to project implementation relevant results; Likewise, the methods and techniques applied allowed to establish the following: On the analysis of the current situation of tourism. The highest percentage of respondents claimed not to know institution or local, regional or national company to report on activities, sites and attractions of Canton Quevedo. 90% of those surveyed considered necessary to apply Communicative Marketing Plans, to promote tourism in the canton Quevedo; well the interview applied to the representative of the tourism department of the Canton Municipal GAD Quevedo said that this institution has not yet implemented projects and plans to promote tourism, and that are in that process. Regarding the situation assessment of tourism Quevedo Canton, the Strengths, Weaknesses, Opportunities and Threats, through the SWOT analysis identified, and so it was established that there are places and tourist attractions; and also the interest of the community and stakeholders to promote and encourage local tourism. Another of the objectives and applied, allowed to establish the elements of the...